Outer Membrane Protein D Gene in Clinical Isolates of Pseudomonas Aeruginosa and its Role in Antibiotic Resistance - Badrosadat Motaghi; Sohrab Najafipour (Fasa University of Medical Sciences, 2015)
Background & Objectives: Pseudomonas aeruginosa is a common cause of nosocomial infection. OprD protein is a specific protein regulating the uptake of carbapenem antibiotic. Loss of OprD is the main mechanism of Pseudomonas Aeruginosa resistance to carbapenem. In this study, the presence of OprD gene is investigated in isolated Pseudomonas Aeruginosa in burn patients of Ghotboddin hospital in Shiraz. Material & Methods: 66 Pseudomonas Aeruginosa were isolated from wound specimens of 250 burn patients. Strain characteristics were confirmed by biochemical tests. Antibiogram was done via disc diffusion method. Finally, OprD gene was investigated by PCR. Results: Isolated Pseudomonas Aeruginosa showed more sensitivity to chloramphenicol and colicitin and more resistance  to ciprofloxacin, gentamycin, cefotaxim, ceftazidin, imipenem, meropenem, and erythromycin. 61 percent of isolates were positive for OprD gene by PCR. Conclusion: The findings of this study revealed that Colicitin and chloramphenicol are more effective in treatment of Pseudomonas Aeruginosa infections in burn patients, and deletion and mutation in OprD gene cause bacterium resistance to carbapenem antibiotic.